การแตกแยกของพรรคการเมืองในรัฐบาลผสม : ศึกษาเปรียบเทียบกรณีรัฐบาลผสมของนายชวน หลีกภัย กับรัฐบาลผสมของนายบรรหาร ศิลปอาชา - จิตสิริ สัจจญาณ (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
This study of internal fragmentation of political parties within coalition government as well as the reallignment of the coalition during the Chuan Leekpai and Banharn Silpa-archa administrations shows that internal fragmenatation of parties under Chuan administration stems from ideological conflicts and conflicting policies with personal conflicts and conflicts of interests as minor causes while, in Banharn administration, the only cause of conflict is the squabble for ministerial posts. The consequence of political fragmentation is instability of the coalition government which weakens parliamentarian system of Thai politics.